A DSM design flow: putting floorplanning, technology-mapping, and gate-placement together - Salek, Amir H.; Lou, Jinan; Pedram, Massoud (DAC 98: DAC: 35th Annual ACM/IEEE Design Automation Conference, 1998)
This paper presents an integrated design flowwhich combines floorplanning, technology mapping, andplacement using a dynamic programming algorithm. Theproposed design flow consists of five steps: maximum treesub-structure formation, levelized cluster tree construction,minimum area implementation using 2-D shape functions,critical path identification, and repeated application ofsimultaneous floorplanning, technology mapping and gateplacement along the timing critical paths. Experimentalresults obtained from an extensive set of benchmarksdemonstrate the effectiveness of the proposed flow.